2014
DOI: 10.1016/j.sjopt.2013.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of dacryocystorhinostomy with and without intraoperative application of Mitomycin C

Abstract: Although the difference between the two groups was not statistically significant, a distinctly higher success was achieved in patients undergoing dacryocystorhinostomy with intra operative Mitomycin C as compared to conventional dacryocystorhinostomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 6 publications
1
14
0
1
Order By: Relevance
“…Of the included studies, the number of patients submitted to Ex-DCR was slightly lower than that submitted to En-DCR. However, the number of subjects who received MMC in Ex-DCR (14 studies) [6,8,11,[22][23][24][25][26][27][28][29][30][31][32], as well as in En-DCR (13 studies) [4,12,21,[33][34][35][36][37][38][39][40][41][42], was similar in both techniques. The clinical heterogeneity is considered the major disadvantage of all the clinical studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the included studies, the number of patients submitted to Ex-DCR was slightly lower than that submitted to En-DCR. However, the number of subjects who received MMC in Ex-DCR (14 studies) [6,8,11,[22][23][24][25][26][27][28][29][30][31][32], as well as in En-DCR (13 studies) [4,12,21,[33][34][35][36][37][38][39][40][41][42], was similar in both techniques. The clinical heterogeneity is considered the major disadvantage of all the clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated larger osteotomy size in DCR surgery with intraoperative MMC application as adjuvant treatment [8,10]. However, according to others, adjuvant use of MMC to prevent failure in Ex-DCR or En-DCR is innocuous and does not change the chance of success of the DCR procedure [3,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In the study conducted by Maniah Quadir, Andleeb Ahangar and colleagues, 13 4 cases (16%) had high tear meniscus height at the end of 6 months compared to 2 cases (13.3%) of our control group. In the MMC group they found 1 eye (4%) with high tear meniscus height, whereas none of our patients in MMC group had a high tear meniscus height postoperatively.…”
Section: Discussionmentioning
confidence: 59%
“…Thus, this finding is an indicator of efficacy of Mitomycin C in preventing DCR stoma stenosis, even though our sample size was smaller. A similar comparative study of DCR with and without application of Mitomycin C was conducted by Maniah Quadir et al 13 in 50 patients of primary nasolacrimal duct obstruction, 51 in which 0.2 mg/mL of MMC was applied over the stoma for 5 minutes. They followed up the patients on 1st day, 1 st , 3 rd , 6 th weeks, 3 rd and 6 th months.…”
Section: Discussionmentioning
confidence: 90%
“…Период наблюдения за паци-ентами после операции также был различным и составлял от 6 до 12 мес [17,18]. Результативность в группе пациен-тов с использованием митомицина-С, по данным различ-ных авторов, составляла от 80 до 95,5% случаев [19][20][21].…”
unclassified